Just like the USA? Critical notes on Alba and Foner's cross-Atlantic research agenda. Issue 13 (20th October 2016) - Favell, Adrian
ABSTRACT: A critical review of Alba and Foner's Strangers No More (2015 ) which focuses on questioning their comparative assimilation of European cases of immigrant integration to the North American, specifically U.S., experience. While this may work in terms of how national immigrant integration has mitigated over time racial discrimination for older, post-colonial migrants, it misrepresents the complex differentiations involved in the super-diversity of recent 'new' migrations within and to Europe. In particular, the variety of types and origins of recent migration is lost in their understanding of the U.K. case, with problems linked to their interpretation of data about minorities and foreigners in the country.